analisis pengaruh ukuran perusahaan, profitabilitas, siklus operasi perusahaan, leverage, dan klasifikasi industri terhadap kualitas laba (studi empiris pada perusahan manufaktur yang terdaftar di bursa efek indonesia periode 2010-2014) - Puji Astuti, Dewi, Dr. Triyono, SE, M.Si (2016)
Earnings information which owned by the manufacturing company will be benefical for the users of financial statements. The purpose of this is to determine the effect of firm size , profitability , operating cycle , leverage , and industry classification on earnings quality companies listed on the Indonesia Stock Exchange (IDX) 2010-2014 . The Method of sampling which used was purposive sampling. The samples are 110 manufacturing companies. The results show that firm size, profitability, operation cycle, and leverage has influence on earnings quality. Whereas, industry classification has no influence on earnings quality. Keywords : Earnings Quality , Company Size , Leverage , Profitability , Industry Classification